Empirical Study of Critical Success Factors for E-Government Implementation in Indonesia Based on Factor Analysis Approach - Napitupulu, Darmawan (Jurnal Bina Praja, 2017)
Many people assume that e-Government is merely a technological problem while in fact non-technological factors also influence it, even tend to be more dominant. Without a comprehensive evaluation covering non-technological aspects, e-Government implementation will fail. This study aims to determine the various factors that affect the implementation of e-Government. The research method used is a survey of several government agencies and the data is analyzed by a quantitative approach, namely factor analysis to confirm success factors that have been obtained in previous synthesis studies (Napitupulu, 2014). The results of the empirical statistical research indicate there are 39 valid and reliable success factors, both technological and non-technological factors in e-Government implementation. Furthermore, these success factors can be classified into four components, namely resource components, levers, values, and impacts. It is expected that all the success factors that have been proven empirically can be accommodated by government agencies, especially in the district/city level to support the successful implementation of e-Government in Indonesia.